Diabetic Cardiomyopathy: Current and Future Therapies. Beyond Glycemic Control - Borghetti, Giulia; von Lewinski, Dirk; Eaton, Deborah M.; Sourij, Harald; Houser, Steven R.; Wallner, Markus (Frontiers in Physiology, 2018)
Diabetes mellitus and the associated complications represent a global burden on human health and economics. Cardiovascular diseases are the leading cause of death in diabetic patients, who have a 2-5-times higher risk of developing heart failure (HF) than age-matched non-diabetic patients, independent of other comorbidities. Diabetic cardiomyopathy is defined as the presence of abnormal cardiac structure and performance in the absence of other cardiac risk factors, such coronary artery disease (CAD), hypertension, and significant valvular disease. Hyperglycemia, hyperinsulinemia and insulin resistance mediate the pathological remodeling of the heart, characterized by left ventricle (LV) concentric hypertrophy and perivascular and interstitial fibrosis leading to diastolic dysfunction. A change in the metabolic status, impaired calcium homeostasis and energy production, increased inflammation and oxidative stress, as well as an accumulation of advanced glycation end products (AGEs) are among the mechanisms implicated in the pathogenesis of diabetic cardiomyopathy. Despite a growing interest in the pathophysiology of diabetic cardiomyopathy, there are no specific guidelines for diagnosing patients or structuring a treatment strategy in clinical practice. Anti-hyperglycemic drugs are crucial in the management of diabetes by effectively reducing microvascular complications, preventing renal failure, retinopathy and nerve damage. Interestingly, several drugs currently in use can improve cardiac health beyond their ability to control glycaemia. GLP-1 receptor agonists (GLP-1RAs) and sodium-glucose co-transporter 2 (SGLT-2) inhibitors have been shown to have a beneficial effect on the cardiovascular system through a direct effect on myocardium, beyond their ability to lower blood glucose levels. In recent years, great improvements have been made towards the possibility of modulating the expression of specific cardiac genes or non-coding RNAs in vivo for therapeutic purpose, opening up the possibility to regulate the expression of key players in the development/progression of diabetic cardiomyopathy. This review summarizes the pathogenesis of diabetic cardiomyopathy, with particular focus on structural and molecular abnormalities occurring during its progression, as well as both current and potential future therapies.